2018
DOI: 10.1038/s12276-018-0095-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical small molecule granzyme B inhibitor improves remodeling in a murine model of impaired burn wound healing

Abstract: Granzyme B (GzmB) is a serine protease that has long been thought to function exclusively in lymphocyte-mediated apoptosis. In recent years, this paradigm has been revisited due to the recognition that GzmB accumulates in the extracellular milieu in many autoimmune and chronic inflammatory disorders, and contributes to impaired tissue remodeling due to the cleavage of extracellular matrix proteins. Knockout studies suggest that GzmB-mediated cleavage of decorin (DCN) contributes to impaired collagen fibrilloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…C57Bl/6J mice were treated topically with MCC950 [1 mg/dose] in 30% pluronic gel, daily from D0 to D4 post-wounding, based on previous studies using small molecule inhibitors topically [ 12 , 13 ]. No significant difference in wound surface was found between MCC950 and gel alone (control) groups ( Figure 1 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…C57Bl/6J mice were treated topically with MCC950 [1 mg/dose] in 30% pluronic gel, daily from D0 to D4 post-wounding, based on previous studies using small molecule inhibitors topically [ 12 , 13 ]. No significant difference in wound surface was found between MCC950 and gel alone (control) groups ( Figure 1 a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Through these cleavages and degradations in the extracellular spaces, GzmB is expected to regulate inflammation, cell adhesion, cell migration, anoikis, coagulation, fibrinolysis, and cell-cell adhesion. Present at low levels in healthy tissue, GzmB is elevated in numerous pathological conditions such as atherosclerosis, rheumatoid arthritis, transplant rejection, acute graft vs. host disease, discoid lupus, drug eruption, atopic dermatitis, impaired burn wound, and photoaging (279, 289297). In these diseases, pathological contributions of GzmB are suggested through not only intracellular apoptotic function but also extracellular proteolytic role.…”
Section: Proteases In Pemphigoid Diseasesmentioning
confidence: 99%
“…Recently, a topical GzmB inhibitor was tested on impaired burn wound murine model, however, there are currently no clinically-approved GzmB inhibitors on the market (289).…”
Section: Proteases In Pemphigoid Diseasesmentioning
confidence: 99%
“…As highly potent inhibitors of the serine proteases in these cascades, SERPINs also play a role in regulating wound healing [28,29]. Therapeutically, some groups have reported that application of recombinant SERPINSs (Alpha-1-antitrypsin, SERPINA1; anti-chymotrypsin, SERPINA3N) and related small molecules can promote wound healing [30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%